2020
DOI: 10.1148/radiol.2020201629
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Prevention, and Treatment of Thromboembolic Complications in COVID-19: Report of the National Institute for Public Health of the Netherlands

Abstract: A potential link between mortality, D-dimer values and a prothrombotic syndrome has been reported in patients with COVID-19 infection. The National Institute for Public Health of the Netherlands asked a group of Radiology and Vascular Medicine experts to provide guidance for the imaging workup and treatment of these important complications. This report summarizes evidence for thromboembolic disease, potential diagnostic and preventive actions as well as recommendations for patients with COVID-19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
332
0
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(381 citation statements)
references
References 40 publications
12
332
0
27
Order By: Relevance
“…9 In terms of preventing and treating venous thromboembolic disease there remains limited evidence or guidance from well-controlled trials on whether low-molecular-weight heparin, unfractionated heparin, direct factor Xa inhibitors, direct thrombin inhibition or other approaches are optimal. 10…”
Section: Discussionmentioning
confidence: 99%
“…9 In terms of preventing and treating venous thromboembolic disease there remains limited evidence or guidance from well-controlled trials on whether low-molecular-weight heparin, unfractionated heparin, direct factor Xa inhibitors, direct thrombin inhibition or other approaches are optimal. 10…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thromboembolic events in patients with COVID-19 has been shown to increase compared to the healthy population. Therefore, when CT shows peripherally located, triangular-shaped consolidation areas, pulmonary thromboembolism, and infarction (Hampton hump) should be considered in the differential diagnosis [44,45].…”
Section: Consolidationmentioning
confidence: 99%
“…Life-threatening thromboembolic events are increasingly identified in COVID-19 patients [44,45,47]. Recently, Grillet and colleagues [44] reported the prevalence of pulmonary embolism (PE) as 23% (n = 23/100) in COVID-19 patients with severe clinical features, and they reported that COVID-19 patients with PE, had a higher requirement for mechanical ventilation than those…”
Section: Pulmonary Embolismmentioning
confidence: 99%
See 2 more Smart Citations